Peta Digital Dusun Pagersari, Mranggen, Srumbung, Magelang Berbasis Aplikasi CarryMap - Emil Adly (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Pagersari is a hamlet located in Srumbung Magelang District, which is planned to be developed into a tourist village. To access the hamlet, a map showing the location and informative information is needed so that tourists can easily reach the location. The hamlet must have an information system containing partial administrative data. The problem often occurs the lack of administrative processing that provides complete, accurate, and easy-to-update data. This service aims to update the hamlet information system by mapping the hamlet, which contains information on population data and other attributes according to the needs based on Geographical Information Systems (GIS) and assisted by using ArcGIS then exported to CarryMap software. The implementation method is collecting population data from family cards, taking coordinate points, and inputting the ARCGIS software. The results obtained are that the public can find out in detail the location of the residents' houses and the population data available in the form of an online map. Therefore, the community can more easily access or update the hamlet population data through the operator. The community can also list the business opportunities they have. With an accurate digital map, it can make it easier for the outside community to find the location of tourist attractions that the village will plan as a tourism village by the potential of each hamlet.